Together but Not Together: Challenges of Remote Learning for Students Amid the COVID-19 Pandemic in Rural South African Universities - Newlin Marongwe; Rufaro Garidzirai (Research in Social Sciences and Technology, 2021)
The purpose of the study was to examine the challenges of remote learning that were faced by students in four rural institutions of higher learning amid the COVID-19 pandemic. It is well documented that in South Africa as well as globally, the COVID-19 pandemic has disrupted the teaching and learning in higher institutions of education. A call was made by the Department of Higher Education and Training that mandated universities to adopt remote learning to save the academic year. That call was a blanket statement that did not consider the context of different universities, given the inequalities that existed prior to the outbreak of COVID-19 between the historically disadvantaged universities and the well-established ones. The study adopted a qualitative approach that made use of a desktop research methodology, as well as the media (Television, radio and newspapers), and social media as sources of data gathering to document the challenges. One of the key findings was that some students studying at rural institutions of higher learning experienced challenges of limited skills as well as the convenience of and access to technology and other tools of trade. The paper concludes that such students were proposing that, ‘we are together but not together”. The root of such grievance is that they were grossly affected by the geographical and historical position of the universities they were enrolled at and the situation was deepened and exposed by the COVID-19 pandemic. The paper recommends the equal redistribution of resources especially to previously disadvantaged Black universities. The paper further recommends that the Department of Education introduce online learning to students from as early as high school so that there will be continuity and ease in remoting learning.